Internal Audit Aspects of Companies' Sustainability Reporting - Antonella Maria TIMIS; Aurelia STEFANESCU (Audit Financiar)
In the current context, dominated by the increasing importance of credible, relevant and timely sustainability information for stakeholders, internal audit is expanding its scope as a key corporate governance actor. Thus, internal audit actively contributes to strengthening corporate governance on optimizing sustainability strategies within companies. The research is two-dimensional. The first dimension includes review of the literature in the field. The second dimension includes a quantitative research aimed at identifying the degree of compliance of companies in the pharmaceutical industry listed on the Bucharest Stock Exchange with corporate governance requirements, in the pandemic and post-pandemic period, complemented by the development of a framework for internal auditing of sustainable corporate governance. The results of the research highlighted the heterogeneity of compliance of the analysed companies with the requirements of sustainable governance but also the need to strengthen internal auditing as a key actor of a solid sustainable governance. They also provide a relevant perspective on how recent events have influenced the corporate behaviour and accountability of these entities in relation to ESG requirements in the pandemic and post-pandemic period.